Web-Based Personnel Data Management Application Design at the North Sumatra Culture and Tourism Office - Harahap, Yunus Fadillah; Satrio, Ilham Hafiz (Journal of Computer Science and Informatics Engineering, 2022)
The development of science and technology has a very important role and its development is very rapid at this time, especially in the field of computer science, many government agencies and private companies have used a computerized system for operational processes that were previously done manually into an automated system in its operation is like a data management process. As for this research, the design of a staffing data management system at the Department of Culture and Tourism of North Sumatra will be carried out, this system is made using the PHP programming language based on the website. The research method that will be used in designing this application is through a process based on the waterfall paradigm method in order to map out the stages of a well-structured basic development. This application is designed to have an impact on the progress of the Culture and Tourism Office of North Sumatra Province in the development of technology which has now entered sophisticated so that agencies need to develop the economy through technology which is expected to be able to present information accurately and accurately and use it more efficiently than the old system. .